2015
DOI: 10.1111/idh.12188
|View full text |Cite
|
Sign up to set email alerts
|

Role of supportive maintenance therapy on implant survival: a university‐based 17 years retrospective analysis

Abstract: Role of supportive maintenance therapy on implant survival: a university-based 17 years retrospective analysis. Role of supportive maintenance therapy on implant survival: a university-based 17 years retrospective analysis Abstract: Objective: The objective of this study was to determine whether professional maintenance appointments were related to a decrease on dental implant loss. Methods: We performed a retrospective review (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 32 publications
2
37
0
Order By: Relevance
“…For instance, it was demonstrated that dental implant failure rate was reduced by 90% in patients who had regular maintenance versus no maintenance. Additionally, for “patients that had <1 maintenance visit/year, failure rate was reduced by 60% compared with no maintenance.” 25 In this respect, it has been reported that patients attending to routine PIMT are significantly less exposed to peri‐implant bone loss progression 12,26 . In a comparative 12‐month study, it was found that PIMT every 4 months potentially reduces risk of developing peri‐implantitis compared with no PIMT (3.7% versus 22.7% at patient level, respectively) 27 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it was demonstrated that dental implant failure rate was reduced by 90% in patients who had regular maintenance versus no maintenance. Additionally, for “patients that had <1 maintenance visit/year, failure rate was reduced by 60% compared with no maintenance.” 25 In this respect, it has been reported that patients attending to routine PIMT are significantly less exposed to peri‐implant bone loss progression 12,26 . In a comparative 12‐month study, it was found that PIMT every 4 months potentially reduces risk of developing peri‐implantitis compared with no PIMT (3.7% versus 22.7% at patient level, respectively) 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the soft tissue thickness provides the advantages of decreasing the soft tissue discoloration and show‐through when a patient has a thin tissue phenotype and the implant or abutment is visible through the tissue. The thickened tissue also provides the restorative dentist more tissue volume by which to develop more idealized crown contours, which has both esthetic and biologic advantages . When the soft tissue phenotype is thin, ridge lapping is often necessary which limits access for cleaning and is not stable esthetically .…”
Section: Discussionmentioning
confidence: 99%
“… ∘Predictably increases soft tissue thickness by 1 mm which decreases show‐through of restorations, abutments, and/or implants ∘Corrects ridge deficiencies to provide a more harmonious soft tissue architecture with adjacent teeth and prosthesis ∘Is often helpful in pontic sites to create a thicker tissue that can be contoured for improved esthetics …”
Section: Focused Clinical Questionmentioning
confidence: 99%